2020
DOI: 10.1055/a-1181-8340
|View full text |Cite
|
Sign up to set email alerts
|

Utility and safety of balloon-assisted enteroscopy in patients with left ventricular assist devices: a retrospective multicenter study

Abstract: Objective and study aims Patients with left-ventricular assist devices (LVADs) have an increased risk of gastrointestinal bleeding, especially from the small bowel, often necessitating evaluation with balloon-assisted enteroscopy (BAE). Our study aimed to assess the periprocedural safety and utility of BAE for gastrointestinal bleeding in patients with LVADs. Patients and methods This was a multicenter retrospective cohort study of adults with LVADs who underwent BAE between January 2007 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…A previous prospective study of 60 patients with SBB reported a therapeutic yield of 57% [ 118 ]. A recent multicenter retrospective cohort study reported a 67.4% therapeutic yield [ 119 ]. In another study considering the timing of endoscopy, earlier enteroscopy had a higher therapeutic yield (100%, 76.9%, and 57.7% at ≤24, ≤48, and ≤72 hours, respectively) [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous prospective study of 60 patients with SBB reported a therapeutic yield of 57% [ 118 ]. A recent multicenter retrospective cohort study reported a 67.4% therapeutic yield [ 119 ]. In another study considering the timing of endoscopy, earlier enteroscopy had a higher therapeutic yield (100%, 76.9%, and 57.7% at ≤24, ≤48, and ≤72 hours, respectively) [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…118 A recent multicenter retrospective cohort study reported a 67.4% therapeutic yield. 119 In another study considering the timing of endoscopy, earlier enteroscopy had a higher therapeutic yield (100%, 76.9%, and 57.7% at ≤ 24, ≤ 48, and ≤ 72 hours, respectively). 120 Therefore, endoscopic hemostasis is recommended for various SB lesions such as bleeding lesions (ulcers or erosions), vascular lesions (angioectasia or Dieulafoy lesions), tumors, and diverticula.…”
Section: Statement 12mentioning
confidence: 96%
“…Deep enteroscopy is frequently requested on patients with severe heart disease or implanted cardiac devices. With proper precautions, these procedures are generally well tolerated to perform [6]. In fact, we prefer to perform enteroscopic investigations for these patients with obscure bleeding because of the higher likelihood of finding actively bleeding lesions [7 ▪▪ ].…”
Section: Procedures Indications May Dictate the Approach To Deep Ente...mentioning
confidence: 99%
“…Los pacientes renales tuvieron una mayor incidencia de resangrado (81 vs. 22%) y necesidad de realizar nuevos estudios y la conclusión es que los pacientes renales tienen mayor frecuencia de resangrados y de transfusiones a pesar de la EAD. Hasan 9 presentó en un estudio multicéntrico retrospectivo sobre la utilidad y seguridad de la EAD en los pacientes con dispositivos de asistencia ventricular izquierda e incluyo a 34 pacientes de los cuales 20 estaban con antiagregantes plaquetarios y 24 con Warfarina, y todos tenían evaluación preanestésica clase IV y no hubo complicaciones anestésicas ni endoscópicas. El alcance diagnóstico fue del 69% para la EMB, 73% para la EDB y 55% para la espiral y el alcance terapéutico respectivamente fue de 67, 73 y 44%.…”
Section: Introductionunclassified